STUDY OF THE EFFECT OF CRYOPRESERVED PLACENTA EXTRACT ON THE PROCESSES OF CYTOLYSIS AND LIPID PEROXIDATION IN CCL4-INDUCED LIVER DAMAGE - I. V. Koshurba (Сучасні медичні технології, 2022)
Abstract. The search for new strategies for the correction of exogenous toxic liver lesions is due to the steady increase in the incidence of hepatitis and cirrhosis among the working population, which is an important medical and social problem.